Unmarketing : Stop marketing. Start engaging - Stratten, Scott. (Wiley, 2012)
Potential and current customers want to be listened to, validated, and have a platform to be heard--especially online. This book shows marketers how to create a mindset and systems that perpetually attract the right customers.